2020
DOI: 10.3897/neobiota.55.46874
|View full text |Cite
|
Sign up to set email alerts
|

In-season leaf damage by a biocontrol agent explains reproductive output of an invasive plant species

Abstract: One of the biggest challenges in classical biological control of invasive weeds is predicting the likelihood of success. Ambrosia artemisiifolia, a North American plant species that has become invasive in Europe, causes economic losses due to health problems resulting from its huge amount of highly allergenic pollen and as a weed to agricultural crops resulting from high seed densities. Here we assessed whether the pollen and seed output of the annual A. artemisiifolia (at the end of the season) is related to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 58 publications
0
6
0
Order By: Relevance
“…The beetle Ophraella can strongly reduce the reproduction and population growth rate of Ambrosia in Europe (Augustinus, Lommen, et al, 2020; Augustinus, Sun, et al, 2020; Schaffner et al, 2020). However, based on our findings, we predict a reduced biocontrol efficacy under climate warming, highlighting the importance of accounting for the interplay between ecological and evolutionary processes in predicting biotic interactions in changing environments.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The beetle Ophraella can strongly reduce the reproduction and population growth rate of Ambrosia in Europe (Augustinus, Lommen, et al, 2020; Augustinus, Sun, et al, 2020; Schaffner et al, 2020). However, based on our findings, we predict a reduced biocontrol efficacy under climate warming, highlighting the importance of accounting for the interplay between ecological and evolutionary processes in predicting biotic interactions in changing environments.…”
Section: Discussionmentioning
confidence: 99%
“…By adding or removing beetles, we maintained c. 50% visual leaf damage from August (after c. 2 beetle generations) to September (after c. 3 beetle generations). Damage levels are variable in the field, but often reach levels of 50% leaf damage by mid‐season (Augustinus, Lommen, et al, 2020). The Ophraella beetles used in all our experiments were from a mixture of five populations collected on repeated occasions within 30 km of the field experimental site.…”
Section: Methodsmentioning
confidence: 99%
“…Based on previous studies, it was found that the best control method for these invasive plants is to forbid produce seeds and consume the existing underground seed banks. For example, mowing or biological control of ragweed (Ambrosia artemisiifolia) in a specific period can reduce its seed yield and consume the seed bank (Basky et al 2017;Lommen et al 2018;Augustinus et al 2020). In farmland, the control can be achieved by formulating a rotation system between different crops to inhibit the germination of giant ragweed seeds and consume its seed bank (Goplen et al 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Based on the study of Zhou et al (2018), the female of O. communa uses primarily olfaction in quest of the host plants, but in the case of upwind directions, visual stimuli (e.g. leaf colour) can assist the insect in allocating its host plants, during which in the reproductive stage of the plant provides a biological sign for its herbivore in the form of the pollen dispersion (Augustinus, Lommen, et al, 2020). A. artemisiifolia growth is highly dependent on the soil disturbance level (Ziska et al, 2007), such as in Northern‐Italy, where is, in general, no soil cultivation after the harvest of cereals.…”
Section: Introductionmentioning
confidence: 99%
“…There are many local‐type studies from Europe and China which give population numbers of O. communa based on observations. Thus, detailed data were provided by Augustinus, Lommen, et al (2020) who predicted the impact of O. communa as a biocontrol agent based on the integrating distribution modelling with climate‐dependent vital rates. This study pointed out that egg hatching success strongly decreased from 80% to 20% when relative humidity drops from 55% to 45% during the day.…”
Section: Introductionmentioning
confidence: 99%